Dynamic Relationship Among Crude Oil Price, Stock Price, and Exchange Rates In Indonesia - Alfikranta Atanta; Sofyan Syahnur; Taufiq C Dawood (Research Collaboration Community (RCC), 2023)
This study aimed to examine the causal relationship among oil prices, JCI stock prices, and exchange rates in Indonesia. Observational data were from the period 2015M01-2020M06. The research analysis model used was Toda-Yamamoto (1995) causality test. The results showed a two-way causal relationship between exchange rates and oil and a one-way relationship between exchange rates and stocks. There was a one-way effect of stocks on oil. Stock shocks occurred due to the influence of the stocks themselves—only 10 percent of the exchange rates and 0.62 percent of the oil price. Meanwhile, oil prices experienced shocks from stocks of 35.95 percent and exchange rates of 20.87 percent. Changes were found in the exchange rates because stocks were 57.21 percent and oil prices were 11.27 percent. It is recommended to control the exchange rates so that the economy becomes stable, explore oil in the country or use renewable energy technology to break away from dependence on fossil oil, and maintain the value of stocks to be strong and stable.